The effects of slaked lime washings and alginate coatings on the physicochemical properties of calamansi (Citrus microcarpa) fruit and juice. - Mameloco, Neri May Gallego
Calamansi (Citrus microcarpa) is native to and one of the most commercially important fruit crops in the Philippines. Citrus juice has been labeled as one of the healthiest and most in demand beverage not only because it contains high concentration of vitamin C but also for its distinctive aroma and taste. Yet, more than 25% of citrus are affected by fungal infections. During postharvest process, fruits may experience countless environmental and handling factors that may affect their quality and shelf life. The objective of this study is to determine the efficacy of slaked lime washings and alginate coatings in maintaining the quality of the Citrus microcarpa fruit. Three treatments were used: 1) 1% NaAlginate coating, 2) 10% Slaked Lime washing and 3) 10% Slaked Lime +1% NaAlginate coating. Physicochemical analysis was used to assess the quality of the fruit namely; weight loss and color. Titratable acidity, pH, total soluble solids and FTIR analyses were also conducted on the juice of the coated fruits. Results of the experiment revealed that the treatments used in the study did not help prolong the shelf-life of the calamansi. The percent weight loss of the treatments was higher compared to the control, except for the slaked lime treatment. The control was found to be more acidic than the treated samples, making it less prone to bacterial spoilage. The physical appearance of the control was observed to be much more acceptable than the treated samples. Overall, there was no significant difference (p<0.05) between the control and the treatments in terms of the evaluated physicochemical attributes.